Vegetation Mapping Information System Model Design Of Tambakrejo Village, Jombang District, Jombang Regency - Anggi Indah Yuliana; Agus Sifaunajah; Elda Inia Agustin (NEWTON: Networking and Information Technology, 2022)
The need for vegetation mapping is very necessary at this time because it can make it easier for users to find out the types of plants that exist in each village and their coordinates. In Jombang Regency, there is no system that implements this vegetation mapping system. This research designs the development of web and mobile-based information systems. The tools used for modeling this system are Flowcharts, Entity Relationship Diagrams, Data Flow Diagrams. The software used is Adobe XD to create system designs and MySql as a programming language. From the design of the system that will be made, it will produce a web of geographic information system for mapping vegetation in Jombang Regency.